Panel V: The Role of the Courts in Separation of Powers Disputes - Kenneth Starr; Stephen Carter; Kenneth Culp Davis (Washington University Law Quarterly, 1990)
In the arena of separation of powers, courts have at times shown discomfort similar to that evident in the sometimes articulated fears of entering the thicket of political questions. Notwithstanding the apparent discomfort, however, courts have tended not to back away from deciding separation-of-powers questions.